One- vs. Three-Fraction Pancreatic Stereotactic Body Radiation Therapy for Pancreatic Carcinoma: Single Institution Retrospective Review - Sutera, Philip Anthony; Bernard, Mark E.; Gill, Beant S.; Harper, Kamran K.; Quan, Kimmen; Bahary, Nathan; Burton, Steven A.; Zeh, Herbert; Heron, Dwight E. (Frontiers in Oncology, 2017)
Background/Introduction: Early reports of stereotactic body radiation therapy (SBRT) for pancreatic ductal adenocarcinoma (PDAC) used single fraction, but eventually shifted to multi-fraction regimens. We conducted a single institution review of our patients treated with single or multi-fraction SBRT to determine if any outcome differences existed. Methods and Materials: Patients treated with SBRT in any setting for PDAC at our facility were included, from 2004-2014. Overall survival (OS), local control (LC), regional control (RC), distant metastasis (DM), and late grade 3 or greater radiation toxicities from the time of SBRT were calculated using Kaplan-Meier estimation to either the date of last follow-up/death or local/regional/distant failure. Results: We identified 289 patients (291 lesions) with pathologically-confirmed PDAC. Median age was 69 (range, 33-90) years. Median GTV was 12.3 (8.6 -21.3) cc and PTV 17.9 (12 - 27) cc. Single fraction was used in 90 (30.9%) and multi-fraction in 201 (69.1%) lesions. At a median follow-up of 17.3 months (IQR 10.1-29.3 months), the median survival for the entire cohort 17.8 months with a 2yr OS of 35.3%. Univariate analysis showed multi-fraction schemes to have a higher 2-year OS 30.5% vs. 37.5% (p=0.019), it did not hold significance on MVA. Multi-fractionation schemes were found to have a higher LC on MVA [HR=0.53, 95% CI (0.33-0.85), p=0.009]. At 2 years, late grade 3+ toxicity was 2.5%. Post-SBRT CA19-9 was found on MVA to be a prognostic factor for OS [HR=1.01, 95 CI% (1.01-1.01), p=0.009], RC [HR=1.01, 95 CI% (1.01-1.01), p=0.02] and DM [HR=1.01, 95% CI (1.01-1.01), p= 0.001] Conclusion: Our single institution retrospective review is the largest to date comparing single and multi-fraction SBRT and the first to show multi-fraction regimen SBRT to have a higher LC than single fractionation.. Additionally, we show low rates of severe late toxicity with SBRT.